Agon of the times: Thomas Docherty versus the university. Issue 9 (21st October 2018) - Gibson, Andrew
ABSTRACT: With reviews of his two most recent books as its basis, this Turning Point pays tribute to Thomas Docherty's major endeavour to chart and indict the progressive decline if not the effective destruction of UK universities over the past 40 and especially the past 20 years. It summarises his project and considers his analysis, not only of the situation of higher education, but its relation to our larger cultural predicament, in detail, the problem being above all the long ascendancy of neoliberalism. It underlines the specific thrust his position and history as a talented and versatile literary theorist and critic gives to his critique, as for example in his accounts of contemporary cliché and doublespeak, and the store he sets by literature as counter-discourse, resistance to the contemporary valuation of identity and transparency, and safeguard of an equivalent of Kant's speculative reason, a space quite separate from the existing state of affairs and present pieties, one that is future-oriented but also richly able to learn from the past. It ends by suggesting the need for a few creative supplements to Docherty's work, not least a more ample recognition of the actual, ungainsayable failure and disintegration of `the left', particularly as engineered by New Labour, and of the extent to which critiques of neoliberal culture might be obscurely but significantly implicated in the objects of their attack.